Strategic Impact of Business Intelligence : A Review of Literature - Tripathi, Anuj; Bagga, Teena; Aggarwal, Rashmi K. (Prabandhan: Indian Journal of Management, 2020)
Review of literature is a very critical part of the research journey. The tenacity of this research was to explain a step-by-step guide to expedite understanding by presenting the critical components of the literature review process. We collected and synthesized business intelligence specific research papers from relevant journals with the help of web aggregator. This research paper discussed the strategy of analyzing 553 business intelligence research papers published from 2007-2018. We utilized exploratory research methodology to analyze the research conducted on BI solutions during the defined period. The research ripened a holistic, theoretically grounded, and relevant approach for reviewing the literature on business intelligence. It specified, defined, and positioned the existing BI solution research and helped identify the areas which need further exploration.